Rukyat as Determination of the Lunar Month Beginning: A Method, Obstacles, and Debate in Indonesia - Zufriani Zufriani; Asa’ari Asa’ari; Jamal Mirdad; Arzam Arzam; Ahmad Izuddin; Anwar M. Radiamoda (Institut Agama Islam Negeri Batusangkar, 2023)
Two calendar systems are developing globally, namely the Syamsiyah system (solar system) and the Kamariah system (lunar system). The lunar system is a calendar used by Muslims and has utility in worship rituals based on the calendar period. Qur’an and Hadith have mentioned this completely, namely, one year consists of twelve months. This study aims to determine the determination of the beginning of the lunar month using the rukyat method and to determine the extent to which the implementation of the rukyat method can be accepted by the Indonesian people. The type of research in this article is qualitative research or also known as naturalistic research methods. The data analysis techniques used were condensation, data presentation, and drawing conclusions. The results of the study show that the rukyat method is one of the methods of determining the lunar month, which has been carried out since the time of the Prophet Muhammad p.b.u.h. and his companions, even today it is still used by Muslims around the world, including in Indonesia. Rukyat is a method of determining the beginning of the lunar month by paying attention to important matters and conditions. As for the obstacles of the sighting as determining the beginning of the lunar month, there are several factors, namely the eye of the observer, the shape of the new moon, weather, seeing, the height of the new moon, the distance of the bow and the observer’s psychology